Genesis of scientific thinking in the Qur'an - Ahmed Shogar, Ibrahim Adam (2011)
This paper proposes the Qur`anic conception on objective method of inquiry in the natural phenomena. It aims to elaborate the genesis of scientific thinking based on Qur`anic approach. It is well known fact that the Holy Qur`an have been an important source of inspiration to investigate in nature. While its basic objective was to establish faith and to create a united moral society, the Qur`an has discussed many issues related to physical world. It talks about astronomy, cosmology, creation of mankind, creation of the universe, and astrophysics. This Qur`anic approach on nature inspired and motivated many of earlier scholars from various nations, ethnicities, cultures, and from different religious backgrounds, to investigate in the natural phenomena. The two generative aspects that needed for innovative research, especially in the natural phenomena, are curiosity and scientific thinking. The dawn of scientific knowledge had begun with curiously and observation. Driven by these two factors, mankind has been trying to find unity and regularity in the diversity of the natural processes. His major objective for investigation in nature has been the same; that is to uncover rules that govern the natural phenomena and to appreciate the Power behind the rules. By curiously, man begins to observe and from observation he formulates theories and builds great history and glorious civilization. The basic objective of this article is to explain genesis of scientific thinking in the Qur`an. The paper especially focuses on the general epistemological parameters in the Qur`anic approach, such as the concept of (Taqdir) and concept of (Sunnatullah), which are necessary for systemic engagement for knowledge inquiry and to establish the foundations of research method. The Qur`anic approach on research motivation, creative and critical thinking will be elaborated.